Праздничные стихи: стихи / А. А. Усачев ; худ. К. В. Тер-Захарянц - Усачев Андрей Алексеевич (Дрофа-Плюс, 2011)
Экземпляры: Тыловайский ФО-5(до) (20120726) / Инвентарный номер: 1 / Цена: 260.99 / Авт.знак: У 74 / ББК: 84(2Рос-Рус)6